Pembiayaan Dalam Administrasi Pendidikan - Febriani, Agilia; Widia, Friska; Daffa, Muhammad Falih (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In the implementation of education, finance and financing are very decisive potentials and are an inseparable part of the study of education financing management. Education Financing Financing is funding provided by one other party to support planned investments, either done by themselves or institutions. In other words, financing is funding that is issued to support investments that have been planned to achieve predetermined goals. Financing is one of the resources that can directly support the effectiveness and efficiency of education management. Budget Finance Cost Trigger Cost Trigger Cost, according to Blocher, is a factor that has an impact on the change in total cost